March 1987 cyclone (blizzard) over the eastern Mediterranean and Balkan region associated with blocking - (:unkn) unknown (AMER METEOROLOGICAL SOC, 1998)
The March 1987 blizzard over the eastern Mediterranean and Balkan regions is investigated. Northern Hemispheric and regional 2.50- and 850-hPa geopotential heights illustrate the formation of blocking over northern Europe and cyclogenesis over the considered area. The 850-hPa analyses and National Centers for Environmental Prediction Eta model simulations are in good agreement. Temporal analyses of temperature and precipitation fields show that a cold air surge over the region resulted in a decrease in the daily temperatures of up to 15 degrees C and a heavy accumulation of snow in the early days of the storm. Spatial analyses of the precipitation field reveal that the most snowfall-affected regions were northwestern Turkey and the Balkan countries.
Keywords: STEP-MOUNTAIN COORDINATE; ALPINE LEE CYCLOGENESIS; CLIMATE-CHANGE; LIFE-CYCLES; URBANIZATION; WINTER; MODEL; TEMPERATURE; ANOMALIES; TURKEY